Whey permeate fermented with kefir grains shows antifungal effect against Fusarium graminearum - Gamba, Raul Ricardo (2016)
The objective of the work reported here was to study the antifungal capability of cell-free supernatants obtained from whey permeates after fermentation by the kefir grains CIDCA AGK1 against Fusarium graminearum growth and zearalenone (ZEA) production. The assays were performed in order to study the conidial germination inhibition -in liquid media- and the effect on fungal growth rate and the Latency phase -in solid media. We observed that fermented supernatants of pH 3·5 produced the highest percentages of inhibition of conidial germination. The dilution and, particularly, alkalinisation of them led to the gradual loss of antifungal activity. In the fungal inhibition assays on plates we found that only the highest proportion of supernatant within solid medium had significant antifungal activity, which was determined as fungicidal. There was no ZEA biosynthesis in the medium with the highest proportion of supernatant, whereas at lower concentrations, the mycotoxin production was strain-dependent. From the results obtained we concluded that kefir supernatants had antifungal activity on the F. graminearum strains investigated and inhibited mycotoxin production as well, but in a strain-dependent fashion. The present work constitutes the first report of the effect of the products obtained from the kefir-grain fermentation of whey permeates - a readily available by-product of the dairy industry - on F. graminearum germination, growth, and toxin production.